Gut-Microbiome Implications in Opioid Use Disorder and Related Behaviors - Herlihy, Bridget; Roy, Sabita (Advances in Drug and Alcohol Research, 2022)
Substance use disorder (SUD) is a prevalent disease that has caused hundreds of thousands of deaths and affected the lives of even more (NCDAS, 2019). Despite its huge impact, there is still no known cure for SUD, or the psychological symptoms associated with drug use. Many of the behavioral consequences of drug use prevent people from breaking the cycle of addiction or cause them to relapse back into the cycle due to the physical and phycological consequences of withdrawal. Current research is aimed at understanding the cause of these drug related behaviors and therapeutically targeting them as a mechanism to break the addiction cycle. Research on opioids suggests that the changes in the microbiome during drug abuse modulated drug related behaviors and preventing these microbial changes could attenuate behavioral symptoms. Additional research is needed to determine the exact mechanism in which the microbiome modulates behavior to determine the best therapeutic course of action.